A high fatigue life spring band steel and method of making same

CN122979733APending Publication Date: 2026-10-27ANHUI XIANGLOU NEW MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611481764.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-22
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]然而,均匀拉伸时表现出的塑性不能直接反映冲裁孔边缘的抗开裂能力

Benefits of technology

[0023](1)通过预先构造低锰粗钢粉、富锰细钢粉和低锰细钢粉的复合原料,并使其经历固态成形及淬火配分,所得弹簧带钢在保持较高规定塑性延伸强度的同时具有较长的弯曲疲劳寿命,可用于高应力弹簧钢加工中的薄带弹性零件。原料配置与热处理相配合,有利于协调接合区域承载和粒内区域变形。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979733A_ABST
    Figure CN122979733A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of spring steel material, in particular to a kind of high fatigue life spring strip steel and preparation method thereof.Mechanical alloying is carried out on carbon-containing low-manganese steel powder and manganese powder according to a mass ratio of 95.3:4.7 to obtain manganese-rich fine steel powder;first mechanical compounding is carried out to mechanically compound the manganese-rich fine steel powder on the surface of low-manganese coarse steel powder;second mechanical compounding is carried out to mechanically compound the low-manganese fine steel powder on the outside of the particles obtained by the first mechanical compounding, so that the manganese-rich fine powder is located between the core of low-manganese coarse steel powder and the outside low-manganese fine steel powder.The composite steel powder is formed into a steel strip by solid-state hot pressing and hot rolling, and then austenitizing, interrupted quenching, partitioning and tempering are carried out.By matching the assembly sequence of the steel powder with the phase transformation treatment, the obtained steel strip has good bending fatigue performance and punching edge crack resistance at a relatively high strength level.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of spring steel materials and powder metallurgy technology, specifically to a high fatigue life spring strip steel and its preparation method. Background Technology

[0002] Spring strip steel is used for coil springs, elastic clips, and other thin strip parts subjected to repeated bending. After punching, bending, and assembly, the steel strip bears cyclic loads, and its service life is affected by both the base strength and the quality of edge processing. High-stress spring steel is typically processed using alloying, rolling, and quenching and tempering to obtain the required elastic load-bearing capacity. As strength increases, the local plastic deformation that the punched edges can withstand decreases, and notches and microcracks generated during shearing can easily become sites of subsequent fatigue crack initiation.

[0003] Patent CN111270155A discloses a method for preparing hot-rolled spring steel strip for seat belts, employing processes such as smelting, refining, continuous casting, and rolling to improve the strip's properties. Patent CN118854025A discloses a method for preparing cold-rolled medium-manganese QP steel based on Mn non-homogenization control, utilizing critical zone annealing, rapid austenitization, and quenching partitioning to improve the balance between strength and plasticity by leveraging the phase transformation sequence in different regions. These methods demonstrate that alloy composition and heat treatment history can influence the mechanical properties of steel.

[0004] However, the plasticity exhibited during uniform stretching cannot directly reflect the crack resistance of the punched hole edge. For strip steel formed by powder solidification, the defects at the particle joint location and the phase transformation and hardening state of its adjacent area affect each other. Simply increasing the overall strength or increasing the content of deformable phase is still difficult to simultaneously coordinate the load-bearing capacity at the joint location, the local deformation of the punched edge, and the subsequent cyclic bending performance. Summary of the Invention

[0005] After the strength of spring strip steel is increased, local cracks are prone to occur at the punching edge, which can become the starting point of cyclic bending. However, simply increasing the overall plasticity may weaken the load-bearing capacity, making it difficult to balance strength, edge crack resistance and fatigue life.

[0006] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:

[0007] (1) Carbon-containing low-manganese steel powder and manganese powder with a nominal purity of not less than 99% are mechanically alloyed at a feeding mass ratio of 95.3:4.7 to obtain manganese-rich fine steel powder;

[0008] (2) The preparation of composite steel powder includes the following steps: (2-1) mechanically composite the manganese-rich fine steel powder onto the surface of low-manganese coarse steel powder; (2-2) add low-manganese fine steel powder to the particles obtained in step (2-1) and mechanically composite the low-manganese fine steel powder onto the outside of the particles obtained in step (2-1) to prepare composite steel powder with low-manganese coarse steel powder as the core and manganese-rich fine steel powder located between the core and the outer low-manganese fine steel powder; the total mass of the three types of steel powder is 100 parts, with low-manganese coarse steel powder being 33-37 parts, manganese-rich fine steel powder being 20-24 parts, and the remainder being low-manganese fine steel powder;

[0009] (3) The composite steel powder is subjected to solid hot pressing and hot rolling to produce a 0.8 mm thick steel strip;

[0010] (4) Heat the steel strip to 880℃ and hold for 25s, then transfer it to a 235℃ salt bath. After the steel strip reaches the bath temperature ±5℃, hold for 10s, then transfer it to a 440℃ salt bath. After the steel strip reaches the bath temperature ±5℃, divide it for 5min, cool it, and then temper it at 200℃ for 30min.

[0011] The carbon-containing low-manganese steel powder, low-manganese coarse steel powder, and low-manganese fine steel powder have a carbon mass fraction of 0.51-0.53%, a silicon mass fraction of 1.4-1.6%, and a manganese mass fraction of no more than 0.1%, with the balance being iron and unavoidable impurities.

[0012] Furthermore, the low-manganese coarse steel powder and low-manganese fine steel powder are obtained by argon atomization of the same low-manganese steel liquid. A portion of the powder is sieved to obtain low-manganese coarse steel powder, and another portion of the powder is mechanically refined and classified to obtain low-manganese fine steel powder.

[0013] Furthermore, the mechanical refining is carried out under argon protection at 350 r / min, with a ball-to-material mass ratio of 15:1. The machine is stopped for 15 minutes of cooling every 30 minutes of grinding, and the total grinding time is 8 hours.

[0014] Furthermore, the low-manganese coarse steel powder has a sieve particle size of 63-75 μm, and the D90 of both the manganese-rich fine steel powder and the low-manganese fine steel powder is no greater than 10 μm. After the mechanical compounding in step (2-2), composite steel powder with a particle size of 90-110 μm is collected.

[0015] Furthermore, the mechanical alloying in step (1) was carried out under argon at 350 r / min for 24 h with a ball-to-material mass ratio of 20:1.

[0016] Furthermore, the mechanical compounding in steps (2-1) and (2-2) was carried out under argon gas at 200 r / min for 60 min, with a ball-to-material mass ratio of 3:1.

[0017] Furthermore, the hot pressing in step (3) is carried out under a vacuum of no more than 10 Pa, with a hot pressing temperature of 870 °C, a pressure of 90 MPa, and a holding time of 12 min.

[0018] Further, in step (3), the 4mm thick strip is hot rolled in six passes at 850°C, and the temperature is restored to 850°C in no more than 2 minutes between passes, and then held for 2 minutes.

[0019] Furthermore, in step (4), after the steel strip enters the interrupted quenching salt bath and the distribution salt bath, it reaches the corresponding bath temperature ±5℃ within 10s.

[0020] The present invention also provides high fatigue life spring strip steel prepared by the above preparation method.

[0021] The low-manganese material in the aforementioned composite steel powder participates in interparticle bonding during solid-state forming. Theoretically, after austenitization and interrupted quenching, the low-manganese core and outer region undergo partial martensitic transformation first, while the manganese-rich region retains more untransformed austenite; during partitioning, adjacent carbon-containing martensite inside and outside the manganese-rich region can supply carbon to the manganese-rich region.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] (1) By pre-constructing a composite raw material of low-manganese coarse steel powder, high-manganese fine steel powder and low-manganese fine steel powder, and subjecting it to solid forming and quenching, the resulting spring strip steel has a long bending fatigue life while maintaining a high specified plastic elongation strength, and can be used for thin strip elastic parts in high-stress spring steel processing. The combination of raw material configuration and heat treatment is beneficial to coordinating the load-bearing capacity of the joint area and the deformation of the intragranular area.

[0024] (2) First, manganese-rich fine steel powder is compounded on the outside of low-manganese coarse steel powder, and then low-manganese fine steel powder is compounded. The resulting steel strip has a better hole-enlarging ability in punching, so that the hole edge and cut edge in the processing of high-stress spring steel can withstand subsequent deformation. This formation sequence links the raw material bonding position with the distribution of manganese in the grain, which is beneficial to reduce local hardening and cracking of the punching edge and improve the processing adaptability of thin strip.

[0025] (3) A low-manganese carbon steel core is configured inside the manganese-rich region. The steel strip has good hole expansion and crack resistance at a similar strength level and maintains bending fatigue performance. The core and the external low-manganese material form adjacent carbon sources before distribution, which helps to alleviate the problem of long carbon transfer distance when the manganese-rich region is thick and reduces the impact of local hardening differences on edge deformation during subsequent cooling. Attached Figure Description

[0026] Figure 1 This is a schematic diagram of the manufacturing process of the spring strip steel of the present invention.

[0027] Figure 2The images show the EPMA-WDS line scans of Mn element in representative particle cross sections of composite steel powder before hot pressing in Example 2 and Comparative Example 1, where (a) corresponds to Example 2 and (b) corresponds to Comparative Example 1.

[0028] Figure 3 This is an X-ray diffraction pattern of the spring strip steel after final tempering in Example 2. Detailed Implementation

[0029] The low-manganese steel powder used in this invention is prepared from iron, carbon, silicon, and manganese raw materials; the manganese powder used is metallic manganese powder with a nominal purity of not less than 99%. The carbon content of the low-manganese steel powder is 0.51-0.53%, the silicon content is 1.4-1.6%, and the manganese content is not higher than 0.1%, with the balance being iron and unavoidable impurities. The mechanical refining, mechanical alloying, and mechanical composite processes described below are all carried out under argon protection, and the grinding wheel is made of iron-based material; particle size D90 represents the particle diameter when the cumulative volume fraction reaches 90%.

[0030] Preparation Example 1:

[0031] 19585g of pure iron was charged into an induction melting furnace, evacuated to a pressure not exceeding 10Pa, and then backfilled with argon before melting. 300g of silicon powder, 105g of graphite, and 10g of manganese powder were added sequentially, and melting continued until the silicon and manganese powders melted and entered the molten steel, and the graphite dissolved into the molten steel. Once all the charge had formed molten steel and reached 1580℃, it was held at that temperature for 5 minutes. Surface slag was removed, and the mixture was atomized with argon gas at a pressure of 5MPa. After cooling, the mixture was sieved, and the low-manganese coarse steel powder that passed through a 75μm sieve and remained on a 63μm sieve was collected.

[0032] Preparation Example 2:

[0033] Take 15000g of the remaining steel powder obtained in Preparation Example 1, load it into a single container with 500g of powder, and grind it at 350r / min with a ball-to-powder mass ratio of 15:1. Stop the machine and cool for 15min every 30min of grinding, and grind for a total of 8h. Collect the powder with D90 not greater than 10μm by argon gas flow classification to obtain low manganese fine steel powder.

[0034] Preparation Example 3:

[0035] 476.5g of the low-manganese fine steel powder obtained in Preparation Example 2 and 23.5g of manganese powder were added to a sealed grinding jar and mechanically alloyed at 350 r / min for 24 h, with a ball-to-powder mass ratio of 20:1. The grinding was stopped and cooled for 15 min every 30 min of grinding. The grinding media were separated and classified, and powder with a D90 of no more than 10 μm was collected to obtain manganese-rich fine steel powder.

[0036] Preparation Example 4:

[0037] 1000g of the manganese-rich fine steel powder obtained in Preparation Example 3 was taken and molded at 600MPa for 30s at room temperature without adding any binder. After demolding, it was mechanically crushed and graded by 53μm and 63μm sieves, and the agglomerates between the two sieves were collected. The material above the sieve was crushed again, and the material below the sieve was remolded. The material was recycled no more than twice to obtain manganese-rich agglomerates.

[0038] Preparation Example 5:

[0039] Take 500g of the manganese-rich fine steel powder obtained in Preparation Example 3, mold it at 600MPa for 30s at room temperature, demold it, and mechanically crush it. Separate it into 25μm and 32μm sieves. The material above the sieve is crushed again, and the material below the sieve is remolded. The material is recycled no more than twice to obtain manganese-rich fine agglomerates.

[0040] Preparation Example 6:

[0041] Take 1400g of the low-manganese fine steel powder obtained in Preparation Example 2, mold it at 600MPa for 30s at room temperature, demold it, and mechanically crush it. Separate it into 83μm and 95μm sieves. The material on the sieve is crushed again, and the material under the sieve is remolded. The material is recycled no more than twice to obtain low-manganese granules.

[0042] Preparation Example 7:

[0043] 220g of the manganese-rich fine steel powder obtained in Preparation Example 3 and 780g of the low-manganese fine steel powder obtained in Preparation Example 2 were added to an induction furnace and melted under argon protection. After the molten steel reached 1580°C, it was held at that temperature for 5 min, then atomized with argon gas at a pressure of 5 MPa and cooled. The resulting powder was ground at 350 r / min for 8 h with a ball-to-powder mass ratio of 15:1. After classification, powder with a D90 of no more than 10 μm was collected to obtain uniform alloy fine steel powder.

[0044] Preparation Example 8:

[0045] Take 900g of the uniform alloy fine steel powder obtained in Preparation Example 7, mold it at 600MPa for 30s at room temperature, demold it, and mechanically crush it. Separate it into 53μm and 63μm sieves. The material above the sieve is crushed again, and the material below the sieve is remolded. The material is recycled no more than twice to obtain uniform alloy granules.

[0046] General methods for steel strip forming and heat treatment:

[0047] 312g of the obtained composite powder was placed into a 100mm×100mm hot press mold cavity. Under a vacuum not exceeding 10Pa, the temperature was raised to 870℃ at 20℃ / min, a pressure of 90MPa was applied, and the temperature was held for 12min to form a strip blank with a thickness of 4mm. After cooling to 300℃ at 10℃ / min, the strip was demolded.

[0048] The strip is heated to 850°C and held for 2 minutes, then hot-rolled in six passes with thicknesses of 3.1 mm, 2.4 mm, 1.85 mm, 1.42 mm, 1.08 mm, and 0.8 mm respectively. Between passes, the strip is reheated to 850°C for no more than 2 minutes and held for another 2 minutes. After the last pass, the strip is cooled to 500°C within 120 seconds, and then cooled to room temperature within 5 minutes.

[0049] The steel strip is heated to 880℃ at a rate of 20℃ / s, held at that temperature for 25 seconds, and then transferred to a 235℃ salt bath. The temperature difference between the strip and the bath temperature is kept within 5℃ for 10 seconds, and held for another 10 seconds after reaching this temperature. It is then transferred to a 440℃ salt bath, and after reaching the bath temperature ±5℃ within 10 seconds, it is divided into portions for 5 minutes, followed by water cooling to room temperature within 30 seconds. Finally, the temperature is increased to 200℃ at a rate of 5℃ / min, tempered for 30 minutes, and then cooled to room temperature within 5 minutes, with the edges trimmed to obtain the spring steel strip.

[0050] Example 1:

[0051] Step (1): 165g of low-manganese coarse steel powder obtained from Preparation Example 1 and 100g of manganese-rich fine steel powder obtained from Preparation Example 3 were mechanically compounded in argon gas and treated at 200r / min for 60min. The ball-to-material mass ratio was 3:1, so that the manganese-rich fine powder adhered to the surface of the low-manganese coarse powder.

[0052] Step (2): Add 235g of the low-manganese fine steel powder obtained in Preparation Example 2, and continue mechanical compounding for 60min at 200r / min in argon atmosphere. The ball-to-material mass ratio is 3:1, so that the low-manganese fine steel powder is compounded on the outside of the previously compounded particles. Separate the grinding media and classify them to collect 90-110μm composite powder.

[0053] Step (3): Process the composite powder obtained by the general method of steel strip forming and heat treatment to obtain spring strip steel.

[0054] Example 2:

[0055] Step (1): 175g of low-manganese coarse steel powder obtained in Preparation Example 1 and 110g of manganese-rich fine steel powder obtained in Preparation Example 3 were mechanically compounded in argon gas and treated at 200r / min for 60min. The ball-to-material mass ratio was 3:1, so that the manganese-rich fine powder adhered to the surface of the low-manganese coarse powder.

[0056] Step (2): Add 215g of the low-manganese fine steel powder obtained in Preparation Example 2, and continue mechanical compounding for 60min at 200r / min in argon atmosphere. The ball-to-material mass ratio is 3:1, so that the low-manganese fine steel powder is compounded on the outside of the previously compounded particles. Separate the grinding media and classify them to collect 90-110μm composite powder.

[0057] Step (3): Process the composite powder obtained by the general method of steel strip forming and heat treatment to obtain spring strip steel.

[0058] Example 3:

[0059] Step (1): 185g of low-manganese coarse steel powder obtained from Preparation Example 1 and 120g of manganese-rich fine steel powder obtained from Preparation Example 3 were mechanically compounded in argon gas and treated at 200r / min for 60min. The ball-to-material mass ratio was 3:1, so that the manganese-rich fine powder adhered to the surface of the low-manganese coarse powder.

[0060] Step (2): Add 195g of the low-manganese fine steel powder obtained in Preparation Example 2, and continue mechanical compounding for 60min at 200r / min in argon atmosphere. The ball-to-powder mass ratio is 3:1, so that the low-manganese fine steel powder is compounded on the outside of the previously compounded particles. Separate the grinding media and classify them to collect 90-110μm composite powder.

[0061] Step (3): Process the composite powder obtained by the general method of steel strip forming and heat treatment to obtain spring strip steel.

[0062] Comparative Example 1:

[0063] 110g of the manganese-rich agglomerates obtained in Preparation Example 4 and 390g of the low-manganese fine steel powder obtained in Preparation Example 2 were mechanically compounded in argon at 200 r / min for 60 min, with a ball-to-powder mass ratio of 3:1. The grinding media were separated and classified, and the 90-110 μm composite powder was collected. The remainder was processed according to the general method of steel strip forming and heat treatment to obtain spring strip steel.

[0064] Comparative Example 2:

[0065] The mechanical compounding in Comparative Example 1 was changed to mixing manganese-rich agglomerates and low-manganese fine steel powder in a drum at 60 r / min for 15 min, and then directly loading the mixture into a hot press mold; the remaining raw materials, dosages, steel strip forming and heat treatment conditions were the same as in Comparative Example 1, and spring strip steel was obtained.

[0066] Comparative Example 3:

[0067] Using 390g of the low-manganese agglomerates obtained in Preparation Example 6 as coarse particles, 110g of the manganese-rich fine steel powder obtained in Preparation Example 3 was added, and the mixture was mechanically compounded in argon at 200 r / min for 60 min, with a ball-to-particle mass ratio of 3:1. The remaining grading, strip forming, and heat treatment conditions were the same as in Comparative Example 1, resulting in spring strip steel.

[0068] Comparative Example 4:

[0069] The manganese-rich fine agglomerates obtained in Preparation Example 5 were used to replace the manganese-rich agglomerates used in Comparative Example 1. After adding 390g of low-manganese fine steel powder, the same mechanical compounding was performed to collect composite powder with a diameter of 40-60μm. The remaining steel strip forming and heat treatment conditions were the same as those in Comparative Example 1 to obtain spring strip steel.

[0070] Comparative Example 5:

[0071] The uniform alloy agglomerates obtained in Preparation Example 8 (110g) were used to replace the manganese-rich agglomerates used in Comparative Example 1, and the low-manganese fine steel powder was used to replace the uniform alloy fine steel powder obtained in Preparation Example 7 (390g). The remaining mechanical compounding, steel strip forming, and heat treatment conditions were the same as in Comparative Example 1, and spring strip steel was obtained.

[0072] Comparative Example 6:

[0073] The raw materials and steel strip forming process of Comparative Example 5 were used. After rolling, the steel strip was first heated to 880℃ and held for 30s, then oil-cooled to room temperature; then annealed at 780℃ for 30min, and then heated to 890℃ at 50℃ / s and held for 1s. Subsequently, interrupted quenching, partitioning and tempering were performed in the same manner as in the general method to obtain spring strip steel.

[0074] Performance testing:

[0075] Each example and comparative example was prepared in 3 batches independently. One sample was taken from each batch for tensile and density testing; three samples were taken from each batch for fatigue testing; and two samples were taken from each batch for pore enlargement testing of the two pore types. All tests were conducted at room temperature.

[0076] Tensile properties: Tested according to GB / T228.1-2021 "Metallic materials, tensile testing - Part 1: Test at room temperature", using rolled thin strip specimens, with an original gauge length of 50 mm, a parallel section width of 12.5 mm, and retaining the steel strip thickness. The specified plastic extension strength Rp0.2, tensile strength Rm, and elongation after fracture were determined respectively, and the results were taken as the arithmetic mean of 3 specimens.

[0077] Density: Weigh out the dry sample by mass m0, immerse it in low-viscosity mineral oil under vacuum at 2 kPa for 30 min, restore normal pressure and continue immersion for 30 min, remove the surface oil and weigh out the mass m1 in air. Suspend the saturated sample in water at 25℃ and weigh out the mass m2 in water. Calculate the density using ρ = m0 × ρw / (m1 - m2), where ρ is the sample density, m0 is the mass of the dry sample in air, m1 is the mass of the saturated sample in air, m2 is the mass of the saturated sample in water, and ρw is the density of water at 25℃, taken as 0.99705 g / cm³; the result is the arithmetic mean of 3 samples.

[0078] Bending fatigue life: 80mm × 10mm rolled strip specimens were used, retaining the steel strip thickness. The cut edges were ground along the length to remove machining burrs. A four-point bending fixture was used, with an outer span of 40mm and an inner span of 20mm. The maximum nominal surface stress was 1100MPa, the stress ratio was 0.1, and the sinusoidal loading frequency was 10Hz. The load was calculated based on the actual thickness of each specimen using σ = 3 × F × (Ll) / (2 × b × t²), where σ is the maximum nominal surface stress, F is the total load applied by the two inner rollers, L is the outer span, l is the inner span, b is the specimen width, and t is the specimen thickness. The failure life was defined as the number of cycles corresponding to a 10% decrease in the specimen's bending stiffness relative to the initial stable value, with a cutoff cycle of 3,000,000 cycles. Nine complete failure data points were processed according to the logarithmic life statistical method described in GB / T24176-2009, and the geometric mean life was reported.

[0079] Hole enlargement rate: Take a square steel strip sample with a side length of 90 mm, and make a hole using a 10 mm punch and a 10.2 mm die, recording the initial hole diameter D0. With the burr side facing away from the conical punch, under a blank holder force of 10 kN, enlarge the hole at a rate of 0.2 mm / s with a punch having a 60° apex angle until the first crack penetrates the thickness of the steel strip. Measure the diameters of the hole in two orthogonal directions and take the average value Dh. Calculate using λ = (Dh - D0) / D0 × 100%, where λ is the hole enlargement rate, Dh is the average diameter in the two orthogonal directions after enlargement stops, and D0 is the initial hole diameter; then take the arithmetic mean of 6 samples.

[0080] Machined hole enlargement rate: Take another sample of the same size, drill it, ream it to 10mm and remove burrs, and measure the initial hole diameter; the remaining enlargement conditions and calculation methods are the same as for punched holes. Test 6 pieces in each group, and take the average value of the results.

[0081] Mn elemental line scan: The pre-hot-pressed composite steel powder was embedded, and the cross-section was ground and polished to establish a conductive path. MnKα was measured using EPMA-WDS at 15kV, 100nA, with a focused beam spot and LiF crystal. Peak counts were performed for 10 seconds per point, with 5 seconds of background on both sides. Calibration was performed using Fe and Fe-Mn standards with known Mn content, followed by ZAF correction. A scan line was taken along the cross-section of a single particle, traversing the internal region, with a step size of 0.5μm, and the Mn mass fraction was reported point by point. The figures show representative cross-sections from Example 2 and Comparative Example 1, respectively.

[0082] X-ray diffraction analysis: The steel strip from Example 2 after final tempering was used. A clean surface was prepared while maintaining consistent planar sampling direction, and electropolishing was used to remove the machining-affected layer. CuKα1 monochromatic radiation was used at a wavelength of 0.15406 nm, 40 kV, 30 mA, with a 2θ scan range of 35–105°, a step size of 0.02°, and 2 seconds per step.

[0083] Table 1 Tensile properties and density of various steel strips

[0084]

[0085] Table 2 Bending fatigue life and hole expansion performance of various steel strips

[0086] Example 1 22.1 43.4 52.7 Example 2 24.0 45.7 53.8 Example 3 24.1 42.5 55.3 Comparative Example 1 19.5 35.3 53.1 Comparative Example 2 14.4 29.1 52.8 Comparative Example 3 13.1 26.2 54.7 Comparative Example 4 16.5 38.3 54.2 Comparative Example 5 10.2 24.4 49.6 Comparative Example 6 21.8 39.2 57.9

[0087] Results analysis:

[0088] Tables 1 and 2 show that Comparative Example 1, in which manganese-rich agglomerates were pre-combined with low-manganese fine steel powder, had a punching hole expansion rate of 35.3%, which was higher than that of Comparative Example 2, which was directly mixed; the geometric mean fatigue life was 195,000 cycles. Pre-forming the steel powder into an internal and external particle distribution is beneficial to improving the bending fatigue performance of the steel strip and the crack resistance of the punching edge.

[0089] After placing the manganese-rich fine powder outside the low-manganese agglomerates, the enlargement rate of the punched hole in Comparative Example 3 was 26.2%, and the enlargement rate of the machined hole was 54.7%. Compared with Comparative Example 1, the order of raw material preparation had a more significant impact on the enlargement performance of the punched hole.

[0090] In Example 2, after pre-filling the manganese-rich region with low-manganese coarse steel powder, the enlargement rate of the punched hole increased from 35.3% in Comparative Example 1 to 45.7%, the geometric mean fatigue life increased from 195,000 cycles to 240,000 cycles, and the specified plastic elongation strength decreased from 1285 MPa to 1257 MPa. This assembly method improved the crack resistance and bending fatigue life of the punched hole edge at a higher strength level.

[0091] The enlargement rates of the machined holes in Example 2 are similar to those in Comparative Example 1, while the enlargement rates of the punched holes differ significantly. This may be related to the differences in local hardening after the reduction of the distribution of adjacent carbon sources inside and outside.

[0092] After reducing the size of the manganese-rich agglomerates in Comparative Example 4, the enlargement rate of the punched holes was 38.3%, which was still lower than that in Example 2.

[0093] Comparative Example 5, which uses uniform alloy powder, has a geometric mean fatigue life of 102,000 cycles and a hole enlargement rate of 24.4%. In comparison, Examples 1-3 improve fatigue life and hole enlargement capability while maintaining a high specified plastic elongation strength.

[0094] Comparative Example 6 used uniform alloy powder and underwent critical zone annealing and rapid austenitization after rolling. Its elongation after fracture was 19.2%, higher than that of Example 2, and its hole enlargement rate was 39.2%, lower than that of Example 2. Different formation methods have different effects on tensile ductility and crack resistance at the punched edge.

[0095] As can be seen from Examples 1-3, increasing the amount of manganese-rich fine steel powder and low-manganese core can improve the elongation after fracture, but the specified ductile strength decreases. The punching hole enlargement rate of Example 2 is relatively high, and the elongation after fracture of Example 3 is relatively high.

[0096] like Figure 2 As shown, the cross-section of the composite steel powder in Example 2 shows two enriched regions of Mn content along the scanning direction, with a low-Mn region in the middle; the Mn-rich region of the cross-section in Comparative Example 1 is concentrated in the interior. This comparison shows the difference in Mn distribution along the selected cross-section between the two composite steel powders, corresponding to their different raw material assembly sequences.

[0097] Figure 3 The diffraction peaks of γ(200), γ(220), and γ(311) are visible, accompanied by the diffraction response of the α / α′ phase, indicating that austenite is retained in the steel strip. This phase information corresponds to the formation process of the steel strip after interrupted quenching, partitioning, and tempering.

Claims

1. A method for preparing high fatigue life spring strip steel, characterized in that, Includes the following steps: (1) Carbon-containing low-manganese steel powder and manganese powder with a nominal purity of not less than 99% are mechanically alloyed at a feeding mass ratio of 95.3:4.7 to obtain manganese-rich fine steel powder; (2) The preparation of composite steel powder includes the following steps: (2-1) mechanically composite the manganese-rich fine steel powder onto the surface of low-manganese coarse steel powder; (2-2) add low-manganese fine steel powder to the particles obtained in step (2-1) and mechanically composite the low-manganese fine steel powder onto the outside of the particles obtained in step (2-1) to prepare composite steel powder with low-manganese coarse steel powder as the core and manganese-rich fine steel powder located between the core and the outer low-manganese fine steel powder; the total mass of the three types of steel powder is 100 parts, with low-manganese coarse steel powder being 33-37 parts, manganese-rich fine steel powder being 20-24 parts, and the remainder being low-manganese fine steel powder; (3) The composite steel powder is subjected to solid hot pressing and hot rolling to produce a 0.8 mm thick steel strip; (4) Heat the steel strip to 880℃ and hold for 25s, then transfer it to a 235℃ salt bath. After the steel strip reaches the bath temperature ±5℃, hold for 10s, then transfer it to a 440℃ salt bath. After the steel strip reaches the bath temperature ±5℃, divide it for 5min, cool it, and then temper it at 200℃ for 30min. The carbon-containing low-manganese steel powder, low-manganese coarse steel powder, and low-manganese fine steel powder have a carbon mass fraction of 0.51-0.53%, a silicon mass fraction of 1.4-1.6%, and a manganese mass fraction of no more than 0.1%, with the balance being iron and unavoidable impurities.

2. The preparation method according to claim 1, characterized in that, The low-manganese coarse steel powder and low-manganese fine steel powder are obtained by argon atomization of the same low-manganese steel liquid. A portion of the powder is sieved to obtain low-manganese coarse steel powder, and the other portion of the powder is mechanically refined and classified to obtain low-manganese fine steel powder.

3. The preparation method according to claim 2, characterized in that, The mechanical refining was carried out at 350 r / min under argon protection, with a ball-to-material mass ratio of 15:

1. The machine was stopped for 15 minutes of cooling after every 30 minutes of grinding, and the total grinding time was 8 hours.

4. The preparation method according to claim 1, characterized in that, The low-manganese coarse steel powder has a sieve particle size of 63-75 μm, and the D90 of both the manganese-rich fine steel powder and the low-manganese fine steel powder is no greater than 10 μm. After the mechanical compounding in step (2-2), composite steel powder with a particle size of 90-110 μm is collected.

5. The preparation method according to claim 1, characterized in that, The mechanical alloying in step (1) was carried out at 350 r / min for 24 h under argon atmosphere, with a ball-to-material mass ratio of 20:

1.

6. The preparation method according to claim 1, characterized in that, The mechanical compounding in steps (2-1) and (2-2) was carried out under argon atmosphere at 200 r / min for 60 min, with a ball-to-material mass ratio of 3:

1.

7. The preparation method according to claim 1, characterized in that, The hot pressing in step (3) is carried out under a vacuum of no more than 10 Pa, with a hot pressing temperature of 870℃, a pressure of 90MPa, and a holding time of 12min.

8. The preparation method according to claim 1, characterized in that, In step (3), the 4mm thick strip is hot rolled in six passes at 850℃, and the temperature is restored to 850℃ in no more than 2 minutes between passes, and then held for 2 minutes.

9. The preparation method according to claim 1, characterized in that, In step (4), after the steel strip enters the interrupted quenching salt bath and the distribution salt bath, it reaches the corresponding bath temperature ±5℃ within 10s.

10. A high fatigue life spring strip steel, characterized in that, It is prepared by any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method for spring steel hot-rolled steel strip for safety belt

    CN111270155A

  • Preparation method of cold-rolled medium-manganese QP steel based on Mn non-homogenization regulation and control

    CN118854025A